The Effect of Leverage, Corporate Governance, and Profitability on Firm Value - Mutyarawati, Herlita; Chandra, Kristian; Leon, Farah Margaretha (Universitas Trisakti, 2024)
This research analyzes the influence of debt on firm value with corporate governance as a variable presumed to moderate the relationship between debt and firm value. The research sample was selected using a purposive sampling method, resulting in 44 non-cyclical consumer sector companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2022. The study results indicate that corporate governance and profitability positively affect firm value, and firm size affects firm value. Corporate governance as a moderating variable can negatively moderate the relationship between debt and firm value. The findings of this study provide insights into institutional ownership, profitability, and firm size that affect firm value. Investors can use this information to conduct risk analysis and inform their investment decisions. Investors should choose companies with strong corporate governance and high profitability, considering institutional ownership in the corporate governance variable. Investors should preferably select companies with high institutional ownership and high profitability to ensure high firm value but choose companies with smaller sizes where the company uses total assets productively.